2015
DOI: 10.1007/s10530-015-1037-6
|View full text |Cite
|
Sign up to set email alerts
|

The structure of biogenic habitat and epibiotic assemblages associated with the global invasive kelp Undaria pinnatifida in comparison to native macroalgae

Abstract: Kelp forests dominate temperate and polar rocky coastlines and represent critical marine habitats because they support elevated rates of primary and secondary production and high biodiversity. A major threat to the stability of these ecosystems is the proliferation of nonnative species, such as the Japanese kelp Undaria pinnatifida ('Wakame'), which has recently colonised natural habitats in the UK. We quantified the abundance and biomass of U. pinnatifida on a natural rocky reef habitat over 10 months to make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 64 publications
1
26
0
Order By: Relevance
“…Aquaculture is also the primary vector of its introduction in Spain (Báez et al 2010). Local expansion has been documented in Brittany, as in UK and Ireland (Heiser et al 2014;Minchin and Nunn 2014;Arnold et al 2016), in the last two decades whereas Mediterranean populations decline, probably as a response to warm temperature and a predicted expansion was not confirmed by field data in Portugal (Veiga et al 2014). There is thus a qualitative invasive trend (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Aquaculture is also the primary vector of its introduction in Spain (Báez et al 2010). Local expansion has been documented in Brittany, as in UK and Ireland (Heiser et al 2014;Minchin and Nunn 2014;Arnold et al 2016), in the last two decades whereas Mediterranean populations decline, probably as a response to warm temperature and a predicted expansion was not confirmed by field data in Portugal (Veiga et al 2014). There is thus a qualitative invasive trend (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative studies have shown that Undaria harbors a distinct and reduced epifaunal and epifloral community when directly compared to native kelp species (Arnold, Teagle, Brown, & Smale, 2016;Raffo et al, 2009). However, as evidence suggests that Undaria is not able to displace native kelps, this does not indicate ecological impact in itself.…”
Section: Ecological Impactsmentioning
confidence: 99%
“…Undaria pinnatifida supports impoverished assemblages compared with native habitat-forming 247 macroalgae (Arnold et al, 2016;Raffo et al, 2009). In Argentina, the larger holdfasts offered by M. 248 pyrifera support higher faunal richness and abundance than U. pinnatifida (Raffo et al, 2009).…”
mentioning
confidence: 99%
“…In Argentina, the larger holdfasts offered by M. 248 pyrifera support higher faunal richness and abundance than U. pinnatifida (Raffo et al, 2009). In the 249 UK the longer-lived holdfasts offered by native perennial kelps support greater richness and biomass 250 of sessile fauna (Arnold et al, 2016). Both studies stated, however, that native kelp species may not 251 be negatively impacted by non-native U. pinnatifida, which may occupy a different niche both 252 spatially and temporally, and community-wide responses to invasion are likely to be complex and 253 context-specific.…”
mentioning
confidence: 99%